Examining the Nature and Causes of Youth Restiveness in New Nyanya, Karu LGA, Nasarawa State, Nigeria - Ezecheta, Maureen Amara (African Journal of Stability and Development (AJSD), 2025)
This study examines the nature and causes of youth restiveness in New Nyanya, a peri-urban settlement within Karu Local Government Area of Nasarawa State, Nigeria. The research forms part of a broader investigation into the effectiveness of community participation in addressing youth restiveness, with this seminar paper focusing specifically on one key objective. Adopting a qualitative research design, data were gathered through semi-structured interviews and focus group discussions with selected youths, community elders, and key informants, including security and youth development officers. The study found that youth restiveness in New Nyanya manifests in cult-related violence, political thuggery, drug abuse, vandalism, and social disorder. These behaviours are driven by a combination of factors, including unemployment, exclusion from governance, family breakdown, peer influence, drug accessibility, and political manipulation. The findings further reveal that the proximity of New Nyanya to Abuja exacerbates feelings of relative deprivation, as youths compare their socio-economic circumstances, unfavourably, with those in the Federal Capital Territory. The study concludes that youth restiveness in the area reflects broader systemic and structural failures rather than mere deviance. It recommends multi-layered responses, including targeted economic empowerment, inclusive youth engagement structures, family and community mentorship, and stronger local governance. The paper contributes to the understanding of youth restiveness as both a social and developmental issue requiring coordinated, context-specific solutions